2016
DOI: 10.18632/oncotarget.10096
|View full text |Cite
|
Sign up to set email alerts
|

Vδ2+ and α/β T cells show divergent trajectories during human aging

Abstract: Chronological aging and a variety of stressors are driving forces towards immunosenescence. While much attention was paid to the main T cell component, α/β T cells, few studies concentrate on the impact of age on γ/δ T cells' characteristics. The latter are important players of adaptive immunity but also have features associated with innate immunity. Vδ2+ are the main component of γ/δ while Vδ1+ T cells expand upon Cytomegalovirus (CMV) infection and with age. The Vδ2+ T cells are not influenced by persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…Contrarily to what happens (and we observed) in αβ Tc, we found no significant correlation between the fraction of CD28-γδ Tc and age. This is agreement with that reported by Tan et al, who found that the proportion of terminally differentiated CD28-CD27-α/β Tc was significantly higher in the elderly compared to the young, but the fraction of CD28-CD27-Vδ2 Tc did not differ significantly between these age groups [215].…”
Section: Cd28 Costimulatory Moleculesupporting
confidence: 93%
“…Contrarily to what happens (and we observed) in αβ Tc, we found no significant correlation between the fraction of CD28-γδ Tc and age. This is agreement with that reported by Tan et al, who found that the proportion of terminally differentiated CD28-CD27-α/β Tc was significantly higher in the elderly compared to the young, but the fraction of CD28-CD27-Vδ2 Tc did not differ significantly between these age groups [215].…”
Section: Cd28 Costimulatory Moleculesupporting
confidence: 93%
“…Vδ2+ cells were reported to have immunoregulatory activity (40, 41). Moreover, these cells can produce large amounts of IFN-γ and/or TNF-α, reflecting their killing and immunomodulatory function in collaboration with other components of the immune system (42, 43). …”
Section: Discussionmentioning
confidence: 99%
“…For the γδ T cells, our work in 2014 suggested that, similar to MAIT, γδ T cells are either not susceptible to cellular aging or they simply do not follow the same rules as αβ T cells [ 86 ]. With further studies in the last two years, the data now seem to converge to the fact that Vδ2 (a subset of the γδ) does not follow the same markers as CD4 and CD8 (at least for CD27, CD28) in terms of cytokine production [ 87 , 88 ]. Eberl et al also tested the biological relevance of ligating KLRG-1 on Vδ2 and it does not have the inhibitory effect as shown on CD4, CD8 and even natural killer (NK) cells [ 89 ].…”
Section: Are the Markers Suitable For All T Cells?mentioning
confidence: 99%